1997
DOI: 10.1113/expphysiol.1997.sp004030
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of vascular tone by low density lipoproteins: effects on L‐arginine transport and nitric oxide synthesis

Abstract: SUMMARYLow density lipoprotein (LDL) plays an important role in atherogenesis. Focal accumulation within the arterial intima of excess amounts of cholesterol-rich LDL leads to the migration and recruitment of monocytes, which then differentiate into macrophages after taking up large amounts of oxidatively modified LDL via their scavenger receptors and become lipid-laden 'foam cells' within the subendothelial space. It is generally accepted that oxidized LDL and hyperlipidaemia impair endothelial-dependent vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…Therefore, a decreased production of NO in our cocultures in the presence of LDL might have contributed to the increased adhesion of THP-1 cells in cocultures when compared to the monocultures. There is, however, no general consensus about the effects of LDL on NO synthesis since oxLDL have been reported either to decrease or to increase cNOS expression [32]. Both in mono- and in coculture, we did not find any influence of LPC or oxLDL on NO release in the presence of THP-1 cells.…”
Section: Discussioncontrasting
confidence: 35%
“…Therefore, a decreased production of NO in our cocultures in the presence of LDL might have contributed to the increased adhesion of THP-1 cells in cocultures when compared to the monocultures. There is, however, no general consensus about the effects of LDL on NO synthesis since oxLDL have been reported either to decrease or to increase cNOS expression [32]. Both in mono- and in coculture, we did not find any influence of LPC or oxLDL on NO release in the presence of THP-1 cells.…”
Section: Discussioncontrasting
confidence: 35%
“…It has been reported that patients with acromegaly have increased plasma concentrations of cholesterol [22], lipoprotein (a) and small dense LDL [23,24], and patients with hypercholesterolemia have impaired endothelium-dependent vasodilatation [25,26]. In fact, it has been shown that oxidized LDL-C impairs NO production [27], which plays a key role in the development of endothelial dysfunction and atherosclerosis [28] by production of reactive oxygen species [29].…”
Section: Discussionmentioning
confidence: 99%
“…47,48) Pravastatin stimulates an increase in nitric oxide (NO) production by cultured endothelial cells similar to the effects seen with acetylcholine. 48) It has been suggested that increased plasma LDL inhibits the active transport of L-arginine (L-ARG) by endothelial cells, 49) uncoupling the L-ARG: eNOS pathway and leading to superoxide anion production. 50) Because both superoxide anion and its reaction product NO, and peroxynitrite produce tissue injury, 51) it is possible that an indirect action of pravastatin may be present to normalize endothelial function by protecting the active arginine transport from injury by LDL, thereby preventing the formation of both superoxide anion and peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%